1998
DOI: 10.1136/hrt.80.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention in coronary heart disease: a randomised trial of nurse led clinics in primary care

Abstract: Objective-To evaluate whether nurse run clinics in general practice improve secondary prevention in patients with coronary heart disease. 1.47, 1.10 to 1.96). There was no eVect on smoking cessation (0.78, 0.47 to 1.28). Of six possible components of secondary prevention, the baseline mean was 3.27. The adjusted mean improvement attributable to intervention was 0.55 of a component (0.44 to 0.67). Improvement was found regardless of practice baseline performance. Conclusions-Nurse run clinics proved practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
173
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(184 citation statements)
references
References 12 publications
4
173
2
5
Order By: Relevance
“…19 Specially trained nurses instructed to follow detailed protocols and algorithms under the supervision of a specialist has been shown to improve diabetes outcomes, 20 as have nurse-led clinics. 21 A Canadian outreach program was effective in lowering blood pressure among people with diabetes living in a rural setting. 22 New strategies and partnerships that include family physicians, nurses and specialists are required if cardiovascular risk factors such as hypertension are to be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…19 Specially trained nurses instructed to follow detailed protocols and algorithms under the supervision of a specialist has been shown to improve diabetes outcomes, 20 as have nurse-led clinics. 21 A Canadian outreach program was effective in lowering blood pressure among people with diabetes living in a rural setting. 22 New strategies and partnerships that include family physicians, nurses and specialists are required if cardiovascular risk factors such as hypertension are to be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that with current models of care, the attainment of these stringent BP targets for patients with diabetes may not be attainable in the majority of cases (13). These observations imply that alternatives to conventional care for patients with hypertension and diabetes are required.Nurse-led clinics (NLCs) can improve care outcomes in some chronic circulatory diseases (14,15). It is unknown whether the intensification of BP management by this approach is more effective than conventional care.…”
mentioning
confidence: 99%
“…Nurse-led psychosocial interventions have been shown to be effective, including in heart disease. 72,73 However, many nurses complained of a lack of time. A previous study 41 has shown that it is possible to have a flexible attitude to time management in primary care in order to manage depression effectively.…”
Section: Timing Of the Interventionmentioning
confidence: 99%